Approaching the Downsizing Limit of Maricite NaFePO4 toward High‐Performance Cathode for Sodium‐Ion Batteries - Liu, Yongchang; Zhang, Ning; Wang, Fanfan; Liu, Xiaobin; Jiao, Lifang; Fan, Li‐Zhen (Advanced functional materials, 2018)
Maricite NaFePO4 nanodots with minimized sizes (≈1.6 nm) uniformly embedded in porous N‐doped carbon nanofibers (designated as NaFePO4@C) are first prepared by electrospinning for maximized Na‐storage performance. The obtained flexible NaFePO4@C fiber membrane adherent on aluminum foil is directly used as binder‐free cathode for sodium‐ion batteries, revealing that the ultrasmall nanosize effect as well as a high‐potential desodiation process can transform the generally perceived electrochemically inactive maricite NaFePO4 into a highly active amorphous phase; meanwhile, remarkable electrochemical performance in terms of high reversible capacity (145 mA h g−1 at 0.2 C), high rate capability (61 mA h g−1 at 50 C), and unprecedentedly high cyclic stability (≈89% capacity retention over 6300 cycles) is achieved. Furthermore, the soft package Na‐ion full battery constructed by the NaFePO4@C nanofibers cathode and the pure carbon nanofibers anode displays a promising energy density of 168.1 Wh kg−1 and a notable capacity retention of 87% after 200 cycles. The distinctive 3D network structure of very fine NaFePO4 nanoparticles homogeneously encapsulated in interconnected porous N‐doped carbon nanofibers, can effectively improve the active materials' utilization rate, facilitate the electrons/Na+ ions transport, and strengthen the electrode stability upon prolonged cycling, leading to the fascinating Na‐storage performance. Maricite NaFePO4 nanodots with minimized sizes (≈1.6 nm) are homogeneously encapsulated in porous N‐doped carbon nanofibers by electrospinning. When evaluated as binder‐free cathode for Na‐ion batteries, the ultrasmall nanosize effect with a high‐potential desodiation process successfully transforms the generally perceived electrochemically inactive maricite NaFePO4 into a highly active amorphous phase, rendering high reversible capacity, exceptional rate‐capability, and unprecedentedly long cycle‐life.